2007
DOI: 10.1038/sj.mt.6300142
|View full text |Cite
|
Sign up to set email alerts
|

An Antibody Delivery System for Regulated Expression of Therapeutic Levels of Monoclonal Antibodies In Vivo

Abstract: Monoclonal antibody (mAb) delivery by gene transfer in vivo may be an attractive alternative to current mAb therapies for applications that require long-term therapy. This article describes a transfer system that allows inducible high-level expression of unmodified mAbs in vivo. A recombinant adeno-associated viral (rAAV) vector is used that comprises an expression cassette consisting of a dimerizer-regulated promoter that drives expression of the antibody heavy and light chains linked by a 2A self-processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
62
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 19 publications
0
62
0
Order By: Relevance
“…21,32,33 Serum levels of 14E1 peaked at over 1000 mg ml À1 at day 56 postinjection and persisted at levels greater than 600 mg ml À1 for over 4 months. Administration of AAV2/1-14E1 prior to tumor challenge resulted in significant inhibition of tumor growth, prolonged survival time and tumor regression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,32,33 Serum levels of 14E1 peaked at over 1000 mg ml À1 at day 56 postinjection and persisted at levels greater than 600 mg ml À1 for over 4 months. Administration of AAV2/1-14E1 prior to tumor challenge resulted in significant inhibition of tumor growth, prolonged survival time and tumor regression.…”
Section: Discussionmentioning
confidence: 99%
“…Many different smallmolecule-regulated gene-expression systems have been developed and incorporated into AAV delivery systems including those induced by tetracycline, Rapamycin and mifepristone. 40,41 Recently, Fang et al 32 demonstrated regulated expression of a full-length antibody following AAV delivery by incorporating the Furin/2A technology with a dual vector Rapamycin system. Further improvements for a gene-regulated AAV system for antibodies could include the incorporation of a one-vector system versus a dual-vector system.…”
mentioning
confidence: 99%
“…, resulted in the expression of antibodies with no residual amino acids (Fang et al, 2007). Proteins expressed in plants could have their 2A extensions removed by endogenous proteinases acting on similar hybrid linker peptides.…”
Section: The Unwanted Tagsmentioning
confidence: 99%
“…, which removes the 2A "tag" [21,38]. The presence of 2A, however, can be used for detection of protein expression and localization using anti-2A antibodies [2,3].…”
mentioning
confidence: 99%
“…Importantly, the co-translational nature of this cleavage means that by including various signal sequences within 2A polyproteins, either up-or downstream of 2A, proteins can be either targeted co-translationally to the exocytic pathway or post-translationally to different cellular compartments [34][35][36]. Of the many 2A peptides identified to date [10,27,37], four have been widely used in biotechnology and biomedicine: F2A, equine rhinitis A virus ("E2A"), porcine teschovirus-1 ("P2A") and Thosea asigna virus ("T2A") ( Table 1) [2][3][4]36,[38][39][40][41][42][43].…”
mentioning
confidence: 99%